Measurement of inclusive differential cross sections for Υ(1S) production in pp̄ collisions at s=1.96TeV - Abazov, V. M. (2005)
We present measurements of the inclusive production cross sections of the Υ(1S) bottomonium state in pp̄ collisions at s=1.96TeV. Using the Υ(1S)→μ+μ- decay mode for a data sample of 159±10pb-1 collected by the D0 detector at the Fermilab Tevatron collider, we determine the differential cross sections as a function of the Υ(1S) transverse momentum for three ranges of the Υ(1S) rapidity: 0<|yΥ|≤0.6, 0.6<|yΥ|≤1.2, and 1.2<|yΥ|≤1.8. © 2005 The American Physical Society.